Basidiospore and protoplast regeneration from raised fruiting bodies of pathogenic Ganoderma boninense - Govender, Nisha Thopla; Mahmood, Maziah; Abu Seman, Idris; Wong, Mui Yun (Polish Society of Microbiologists, 2016)
Ganoderma boninense, a phytopathogenic white rot fungus had sought minimal genetic characterizations despite huge biotechnological potentials. Thus, efficient collection of fruiting body, basidiospore and protoplast of G. boninense is described. Matured basidiocarp raised under the glasshouse conditions yielded a total of 8.3 x 104 basidiospores/ml using the low speed centrifugation technique. Mycelium aged 3-day-old treated under an incubation period of 3 h in lysing enzyme from Trichoderma harzianum (10 mg/ml) suspended in osmotic stabilizer (0.6 M potassium chloride and 20 mM dipotassium phosphate buffer) yielded the highest number of viable protoplasts (8.9 x 106 single colonies) among all possible combinations tested (regeneration media, age of mycelium, osmotic stabilizer, digestive enzyme and incubation period).